Cryptogenic focal epilepsy and "hidden" celiac disease in adulthood: a causal or accidental link?. (2nd December 2015) - Casciato, Sara; Morano, Alessandra; Albini, Mariarita; Fanella, Martina; Lapenta, Leonardo; Fattouch, Jinane; Carnì, Marco; Colonnese, Claudio; Manfredi, Mario; Teresa Giallonardo, Anna; Di Bonaventura, Carlo
Abstract : Purpose. Celiac disease (CD) is an immuno-mediated small bowel disease characterized by chronic inflammation due to a permanent intolerance to gliadin. Several neurological complications have been described, including epilepsy, whose evolution might often improve by adopting gluten-free diet (GFD). We studied a population of adult patients affected by posterior drug-resistant epilepsy of unknown cause by performing an accurate screening for CD. In the selected patients presenting the association of epilepsy and CD, we characterized the related electro-clinical features. Materials and Methods . We consecutively identified 211 adult subjects affected by drug-resistant cryptogenic focal epilepsy with posterior seizures. All these patients underwent serological screening for CD. In 10 subjects positive serological tests allowed to perform a CD diagnosis (confirmed by duodenal biopsy). For each patient clinical and EEG data, neuroimaging studies, serological and histological findings were revised, as well as response to GFD, defined as an improvement in seizure outcome. Results. A significant delay between diagnosis of epilepsy and CD was documented. Visual ictal manifestations were reported in half of subjects. In all cases, interictal EEG showed slow and epileptiform abnormalities over parietal-occipital and temporal regions; in three cases, FOS phenomenon was observed. Four patients had familiar history of CD and six cases showed clinical signs/symptoms of malabsorption. GFD led to a reduction of seizure frequency in half of patients. Conclusions . "Posterior" ictal semiology, peculiar EEG patterns and drug-resistance emerge as the most interesting characteristics. CD screening should be performed in epilepsy patients presenting such features.